2019
DOI: 10.1016/j.ihj.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of urinary cotinine with cardiovascular risk factors in pan masala tobacco users

Abstract: Background Tobacco consumption is considered as one of the major risk factors for cardiovascular (CV) morbidity. However, the effect of paan masala tobacco (PMT) (a type of smokeless tobacco) consumption has not been well studied in our context. Our study is aimed to find an association of CV risk factors between PMT users and nonusers and to correlate those parameters with urinary cotinine level, a degradation product of nicotine occurring in tobacco. Methods This comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…28 Another cross-sectional study found total cholesterol, triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) significantly higher in pan masala tobacco chewer. 29 In a prospective Swedish study with a follow-up of 8 years found 1.5 times higher risk of ischemic and 1.6 times risk of total stroke in nonsmoking Snus user as compared with nonusers. 30 A Swedish study analyzed the all-cause mortality of falsely promoted safe product so called Snus.…”
Section: Smokeless Tobacco and Cardiovascular Diseasesmentioning
confidence: 97%
“…28 Another cross-sectional study found total cholesterol, triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) significantly higher in pan masala tobacco chewer. 29 In a prospective Swedish study with a follow-up of 8 years found 1.5 times higher risk of ischemic and 1.6 times risk of total stroke in nonsmoking Snus user as compared with nonusers. 30 A Swedish study analyzed the all-cause mortality of falsely promoted safe product so called Snus.…”
Section: Smokeless Tobacco and Cardiovascular Diseasesmentioning
confidence: 97%
“…Hasil penelitian tersebut kadar kotinin urin berkorelasi positif dengan kadar kolesterol LDL serum pengguna tembakau dengan nilai 0,500 (p<001). 30 Hasil analisis deksriptif menunjukkan terdapat dua subyek yang memiliki nilai kolesterol LDL serum tertinggi dan merupakan outlier dalam data subyek yang berhasil dikumpulkan. dilakukan eksklusi pada data subyek tersebut dan hasil akhir didapatkan subyek berjumlah 122 orang.…”
Section: Pembahasanunclassified
“…35 Penelitian korelasi status merokok yang menggunakan kotinin dan kolesterol LDL untuk membuktikan adanya pengaruh asap rokok yang mengandung nikotin terhadap resiko PJK yang berasal dari profil lipid telah dilakukan sebelumnya. 5,9,16,30 Penelitian lain mendapatkan hasil berbeda, dimana peningkatan kotinin serum memiliki korelasi tidak bermakna dengan profil lipid, yang disebabkan oleh desain penelitian potong lintang yang mengambil paparan asap rokok bersifat jangka pendek, sementara efek paparan asap rokok mungkin baru dapat dilihat dalam jangka panjang. 29 Adanya pengaruh dari waktu pengukuran paparan asap rokok terhadap biomarker yang digunakan, menyebabkan perlunya biomarker dengan jangka waktu lebih lama dari kotinin serum atau biomarker faktor resiko PJK yang dapat dideteksi dalam jangka waktu pendek.…”
Section: Pembahasanunclassified
“…These factors were related to oxidative stress and inflammation mechanisms, especially cigarette smoke, which plays a significant role in CVD development. [3][4][5][6] Smoking behaviour is a common habit in many countries. Indonesia is ranked third with the highest number of smokers in the world (9.91 million), after China (26.5 million) and India (19.8 million).…”
Section: Introductionmentioning
confidence: 99%